2019
DOI: 10.1039/c8ra08801b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of highly conductive PEDOT:PSS via surfactant templates

Abstract: The electrical conductivity of 1879.49 ± 13.87 S cm−1 was achieved for PEDOT:PSS, which is the highest value reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 62 publications
(72 reference statements)
4
79
0
1
Order By: Relevance
“…Also, we noticed a lack of peaks around = 600 nm, which indicated that the PEDOT chains preserved their oxidation state as previously reported by Heuer et al [48]. Finally, the UV-Vis signal of the PEDOT:PSS nanospheres for > 900 nm remained constant, also supporting the fact that the nanospheres fabrication process did not alter the chemical nature of the PEDOT:PSS complex [49][50].…”
Section: Methods Liquid Dispersions Were Characterized By Dynamic LIsupporting
confidence: 88%
“…Also, we noticed a lack of peaks around = 600 nm, which indicated that the PEDOT chains preserved their oxidation state as previously reported by Heuer et al [48]. Finally, the UV-Vis signal of the PEDOT:PSS nanospheres for > 900 nm remained constant, also supporting the fact that the nanospheres fabrication process did not alter the chemical nature of the PEDOT:PSS complex [49][50].…”
Section: Methods Liquid Dispersions Were Characterized By Dynamic LIsupporting
confidence: 88%
“…Pre-treatment methods involve the simple addition of polar, protic, and aprotic organic solvents miscible with water, such as N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and ethylene glycol (EG) [32,33,[35][36][37], or of organic compounds that get dissolved in water, such as sorbitol [33,38,39], as well as the incorporation of low-viscosity and transparent ionic liquids like 1-ethyl-3-methylimidazolium tetracyanoborate (EMIM BTI) [16,29] and ionic/non-ionic surfactants like cetrimonium bromide (CTAB), sodium dodecyl sulphate (SDS), and polyethylene glycol p-(1,1,3,3-tetramethylbutyl)-phenyl ethers (Triton X-100) into the aqueous dispersion of PEDOT:PSS [11,40]. The addition of pre-treatment agents (dopants) into the polymer solution will substantially affect the electrical conductivity, transmittance, and morphology of the formed films.…”
Section: Pre-treatment Methodsmentioning
confidence: 99%
“…Even though PEDOT has substantial electrical conductivity, it is insoluble in drinking water, rendering it difficult to process. [ 47 ] To enhance the solubility and dispersibility of PEDOT, it is usually doped with a water‐soluble polyelectrolyte, PSS. The presence of sulfonate (SO3) and sulfonic acid groups (SO3 H + ) aid the dissolution of PEDOT by balancing the charge on it.…”
Section: Overview Of the Synthesis Of Pedot:pssmentioning
confidence: 99%